Disposal of Liquid Combustible Wastes using Flameless Burners with Porous Carbon Matrix - Dolgov S. V. Sergey Viktorovich; Savchenko E. Evgenii; Khaustov S. A. Sergey Aleksandrovich; Tabakaev R. B. Roman Borisovich; Zavorin A. S. Aleksandr Sergeevich (2016, 2016)
Title screen